2008
DOI: 10.1589/jpts.20.51
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variation in Cushion Thickness on the Sit-to-Stand Motion of Elderly People

Abstract: Abstract. This study was done to investigate whether cushion thickness affected elderly people during the sit-to-stand motion (STS motion). Fourteen elderly subjects aged 79 or over were recruited from the outpatients at a rehabilitation clinic. Their STS motions were evaluated and analyzed using a digital video camera and analyzing software. As the thickness of the cushion increased, it was difficult to identify the pelvic movement during STS motion, although the trunk was inclined more anteriorily and the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Therefore, they suggest that patients should be positioned with the affected foot behind the unaffected one for symmetrical knee moment during performance of STS. Similarly, Masaya et al20 ) reported that cushion thickness affected STS motion among the elderly. They elucidated that increased cushion thickness induced inclined trunk anteriority and required greater knee extensor strength during STS motion.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, they suggest that patients should be positioned with the affected foot behind the unaffected one for symmetrical knee moment during performance of STS. Similarly, Masaya et al20 ) reported that cushion thickness affected STS motion among the elderly. They elucidated that increased cushion thickness induced inclined trunk anteriority and required greater knee extensor strength during STS motion.…”
Section: Discussionmentioning
confidence: 85%
“…Standing up from the sitting position Anan (2008) [17] x x x 9 75.0 Yes Anan (2015) [6] x x x x 8 66.7 Yes Burnfield (2012) [3] x x x x 8 66.7 Yes cacciatore (2011) [20] x x x 9 75.0 Yes Fotoohabadi (2010) [11] x x 10 83.3 Yes Gilleard (2008) [19] x x 10 83.3 Yes Ikeda (1991) [23] x x x x x 7 58.3 No Johnson (2010) [21] x x x 9 75.0 Yes Johnson (2010) [22] x x x 9 75.0 Yes Kinoshita (2015) [25] x x 10 83.3 Yes Kim (2014) [26] x x x 9 75.0 Yes Leardini (2011) [27] x x x x 8 66.7 Yes Park (2014) [28] x [29] x x x x x x 6 50.0 No (1) Is the objective and hypothesis of the study clearly described? (2) Are the main outcomes to be measured clearly described in the introduction or materials and methods section?…”
Section: Qualitymentioning
confidence: 99%
“…Alexander et al 4) reported that aging affects STS acquisition, and that older adults with difficulty performing this maneuver require prolonged STS time. We reported that older subjects who experienced dif- The coordination of joint movements during STS motion 45 ficulty with this motion performed the STS using less energy and with more consideration for stability, relative to younger healthy subjects 5) . It is important to control the redundant degrees-offreedom (DOFs), which coordinate with each body segment to accomplish tasks.…”
mentioning
confidence: 95%